Caregiving and future planning perspectives of siblings of individuals with intellectual and developmental disabilities: Insights from South Korea, Japan and Taiwan. Issue 1 (24th September 2022) - Lee, Chung Eun; Hagiwara, Mayumi; Chiu, Chun‐Yu; Takishima, Mayu
Abstract: Background: As individuals with intellectual and developmental disabilities age, their siblings are more likely to assume caregiving responsibilities. However, little is known about experiences of East Asian siblings with respect to their caregiving and future‐planning within their own country, as well as other East Asian countries. Methods: Using a national survey, this study explored experiences of 576 siblings across South Korea, Japan and Taiwan. Results: A common factor across the three countries was that siblings were less engaged in advocacy and future‐planning activities and felt less competent to play the role of caregiving. Korean siblings reported more negative views about disability, while Japanese siblings reported less engagement in future‐planning and Taiwanese siblings reported greater involvement in caregiving. Conclusion: Based on 'universalism without uniformity', it is recommended to develop culturally sensitive sibling‐targeted intervention based on each country's context.